Importance and influence of sensorimotor exercises of the knee joint muscles on body stability - Siminska, Joanna; Baczyński , Łukasz; Kitschke, Ewa; Nowacka, Krystyna (Journal of Education, Health and Sport, 2022)
Introduction: The concept of prioprioception, known as a conceived solution, which is formed from prioprioceptors that reach the spinal cord, may give rise to reflex reactions. In all changes to a change that affect the behavior of the data, it should be noted that it is recorded, and that it is appropriate and appropriate. What is dependent reaction to change, reaction to change reaction to change, behavior change, change in orientation is a change? Aim of the study: The aim of the study is to assess the effect of the sensorimotor muscles of the knee joint on the muscles. The improvement point was assessed. Material and methods: 20 patients tested fabrics. Among women and 9 men. In order to improve the company’s condition, streamlining the technique of the technique on the Easy Tech balancing platform. A fitting with a radius of 20 cm was used in the tests. You repair the research group on the platform twice. The first test was performed immediately after the warm-up, the next test was performed by the knee joint doctor after the running and independent education. Effect on the improvement of treatment outcomes In tests shown to cut sex for performance. Reaching for the improvement of health and improvement of the client’s condition. Conclusions: The technology used, a one-time method of sensorimotor training, to improve the results of users of knee injuries. One-time sensorimotor training, the doctor of the knee joint did not show a differential calculation of statistical statistics in relation to the significance of BMI. Note a weak positive correlation, not statistically significant, showing that the heavier person improved the results.